The Influence of the Period of Retention on the Reliability of Episodic Memory in the Context of Testimony - Baić, Valentina; Oljača, Milan; Tasić, Marija (NBP. Nauka, bezbednost, policija, 2022)
The paper presents a study that aimed to examine the reliability of episodic memory by varying the retention time from the moment of initial observation of two incidents to the moment of communicating what had actually been remembered. Ninety (90) students aged from 21-26 years, from the University of Criminalistic and Police Studies participated in the research (50 males and 40 females). The interval of retention presented an independent variable on four levels: T1 (immediately after watching a recording), T2 (after 1 month), T3 (after 3 months) and T4 (after 6 months). The accuracy of remembering one aspect of the incident is a dependent variable: characteristics of the event, characteristics of the perpetrators and characteristics of the victim. Results suggest that memory accuracy declines dramatically after a month (T2), but also after three and six months, when the downward trend in memory accuracy is less pronounced. Regarding the degree of confidence in memory accuracy, the pattern of results is practically identical to that of memory accuracy. As a whole, the results indicate that the retention interval strongly affects both accuracy and certainty in memory accuracy, regardless of the type of crime and the characteristics being evaluated.